Fulminant Laryngeal-tracheobronchial-pulmonary Aspergillosis: A Rare and Fatal Complication in Allogeneic Hematopoietic Stem Cell Transplantation Recipients - Tao, Tao (Intern Med, 2017)
A 23-year-old man who had previously undergone allogeneic hematopoietic stem cell transplantation (allo-HSCT) for severe aplastic anemia was diagnosed with invasive laryngeal-tracheobronchial-pulmonary aspergillosis after presenting with a persistent dry cough at six months post-transplantation based on the findings of laryngoscopy and fiberoptic bronchoscopy. A fiberoptic bronchoscope was used to remove the obstructive material from the patient's airway and posaconazole plus caspofungin were administered to successfully to treat the patient. Our report suggests that laryngoscopy and fiberoptic bronchoscopy should be considered as alternative approaches to the diagnosis and treatment of allo-HSCT recipients with persistent respiratory symptoms when invasive laryngeal aspergillosis and invasive tracheobronchial aspergillosis are suspected.